Factors Affecting Quality of Life and Psychosocial Needs Among Young Syrian Breast Cancer Women: A Mixed-Methods Study - SHAZA, HASAN (BMC Women’s Health, 2023)
The diagnosis and treatment of breast cancer are very distressing for young women and can result in a lot of unmet psychosocial needs and a lower quality of life. Knowledge gaps in the literature remain about addressing and identifying the psychosocial needs and quality of life of breast cancer women living in countries in ongoing crises, such as Syria. This study aimed to determine the factors affecting the quality of life and psychosocial needs of young Syrian breast cancer women. A mixed-methods explanatory sequential design was used with an initial quantitative survey conducted on 167 young breast cancer women at Tishreen University Hospital in Latakia. The data was collected using the Psychosocial Needs Inventory, the Cognitive Appraisal of Health Scale, a Modified Ways of Coping—Cancer Version, and the Quality of Life Questionnaire—Breast Cancer Patient Version. The quantitative survey was followed by semi-structured qualitative interviews with 11 participants who had already completed the quantitative survey. Thematic analysis was used to analyse the qualitative data using NVivo 10 software. The quantitative results showed that the highest percentage of unmet psychosocial needs was reported for practical needs (40.05%), followed by information needs (38.14%), child care needs (36%), interaction with health professionals needs (25.1%), identity needs (24.84%), emotional and spiritual needs(24.44%), and support network needs (19.9%). The results also showed that the challenge appraisal was the most predominant among the participants (M = 3.66, SD = 0.574), followed by harm/loss, benign, and threat appraisals. Spirituality and positive restructuring were the most frequently used strategies (M = 3.87), followed by seeking social support and making changes (M = 3.54). The results also showed low overall quality of life (M = 5.24, SD = 1.186), a low level of physical well-being (M = 5.10, SD = 1.883), a very low level of psychological well-being (M = 4.51, SD = 1.607), a very low level of social well-being (M= 4.28, SD = 1.469), and a high level of spiritual well-being (M = 7.07, SD = 1.378). The hierarchical multiple regression revealed that the level of education, challenge appraisal, harm appraisal, spirituality, wishful thinking, and detachment were predictors of the quality of life. All six variables explained 44.7% of the variance in the quality of life. The qualitative results identified eight major themes: (1) Challenges of adequate information needs with five subthemes (inadequate communication with health professionals, lack of educational programs and awareness campaigns, inadequate number of nurses, need for nutritionists, and effects of unmet informational needs); (2) Psychological challenges with four subthemes (uncertainty of the future, fear for the children, treatment-related effects and the loss of a woman’s identity, and inadequate psychological support from the health professionals); (3) Financial challenges with three subthemes (treatment is expensive and not available, low incomes and high cost of living, and other financial challenges); (4) Social influences with two subthemes (society’s view and stigma, lack of marriage choices); (5) Cancer invaded my whole life with three subthemes ( psychological effects, unmet family and child care needs, and physical effects); (6) Factors affecting the quality of life with two subthemes (factors that worsen life, and factors that improve life); (7) Environmental stressors (stressful hospital environment); (8) Coping strategies with four subthemes (acceptance and challenge of the disease, religion and spiritual practices, social support, and other coping strategies). Young breast cancer women living in countries in crisis have high levels of unmet needs across a wide range of psychosocial areas and a low quality of life. Healthcare professionals, therefore, should tailor strategies that could help their patients meet their needs and improve their quality of life.